Effect of Cryptocurrency Marketplace Incentive Distribution with Burning Token Method on Halal Crypto Exchange Token Value - Rendy Ardiansyah; Ibnu Khajar (Universitas Darussalam Gontor, 2023)
At the beginning of the 21st century, one of the most in-demand technology investments was blockchain/cryptocurrency technology. Cryptocurrency usage globally has increased from 106 million in January 2021 to 295 million users in December 2021 or an increase of 178% in 2021. The world market capitalization value of cryptocurrency has increased from 787 billion dollars in January 2021 to 2.3 trillion dollars in December 2021 or an increase of 192% in 2021. In the Cryptocurrency world, one method of sharing incentives is to